A business process modeling-enabled requirements engineering framework for ERP implementation. Issue 3 (1st June 2015) - Panayiotou, Nikolaos A.; Gayialis, Sotiris P.; Evangelopoulos, Nikolaos P.; Katimertzoglou, Petros K.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe and analyze the benefits of the application of a requirements engineering framework to assist Enterprise Resource Planning (ERP) development. This framework combines the technology-driven and the process-driven approaches for requirements analysis and implementation. Specific business process modeling methods enhance the framework and assist the formulation of the functional specifications of the ERP system and the management of requirements. Design/methodology/approach – A case study strategy was chosen as the most appropriate method to answer the research question and test the theoretical propositions. The case study's unit of analysis is a Greek manufacturing company and its ERP implementation project. A requirements engineering framework enhanced with business process modeling methods was applied and the results were evaluated using metrics for ERP implementation success. Data were collected using multiple sources of evidences, including interviews with various stakeholders, structured questionnaires, direct observations, vendors' functionality papers and company's documentation. Findings – This study proves that the configuration of ERP's reference models together with the adjustments of organization's processes, provided through a structured requirements engineering framework can lead to reliable functional specifications, a smooth transition to an ERP system and, eventually, to successful ERP implementation, concerning its alignment with requirements. Research limitations/implications – A single case study is conducted in a typical manufacturing company, providing opportunities for further research in other industries, testing in parallel well-defined requirements and other success factors for ERP implementation. Originality/value – The paper fulfils the identified needs for applied methodologies and frameworks for requirements engineering which can assist successful ERP implementations.